ANDULANG VILLAGE GOVERNMENT POLICIES IN DEVELOPING THE BUSINESS OF A TILE CRAFTER IN SUMENEP DISTRICT - yasin, Il (JURNAL SETIA PANCASILA, 2022)
One of the national development priorities currently being carried out by the government is strengthening the local economy. One form of activity that can be carried out by the government is to encourage the growth of a business climate in community groups, including the community craft business sector. The precarious craft in Andulang village is a craft in Sumenep district which is still surviving in the midst of competition in the precarious craft business from several other areas. The purpose of this study was to find out how the implementation of Andulang Village government policies in developing small tile craft industry businesses and to analyze the level of welfare of small tile craft industry entrepreneurs. Through a descriptive qualitative approach, data were obtained through interview, observation and documentation techniques. The results of this study indicate that the Andulang village government institutionally already has a policy scheme set out in the 2021 Village RPJM whose aim is to encourage the tile craft business climate to continue to survive both through coaching activities for craftsmen groups and in the form of distributing aid for production equipment. Through the village government's intervention scheme for the keris craft sector, it turns out that it can help add value to the production and income of the craftsman community.